THROMBOCYTOPENIA IN PLASMODIUM FALCIPARUM MALARIA - Ansari, Shuaib; Khoharo, Haji Khan; Abro, Allauddin; Akhund, Israr Ahmd; Qureshi, Fatima (Journal of Ayub Medical College Abbottabad, 2009)
Background: Malaria is usually associated with reduced blood cell counts & mild to moderate thrombocytopenia is a common association of malaria. The cause of thrombocytopenia is poorly understood, but the immune-mediated lysis, sequestration in the spleen and dyspoietic processes in the marrow with diminished platelet production have all been postulated. This study was conducted to evaluate thrombocytopenia in the patients suffering from acute Plasmodium falciparum malaria. Methods: This descriptive case series study was conducted at a tertiary care hospital, Liaquat University of Medical & Health Sciences Jamshoro, over a one-year period. A total of 370 Plasmodium falciparum positive on peripheral blood film were studied. Full blood counts were determined by using automated Coulter analyzer. Thick & thin smears were stained with Giemsa stains and studied by haematologist. Data was analyzed using the SPSS version 10.0. Results: Out of 370 patients, 260 were male & 110 were female, with M:F ratio of 2.36:1. Mean age was 34±1.7 years (range 16-53 years). Haemoglobin values were 12.7±1.4g% and white blood cells counts were found 12600±450/µL. Out of 370, 114 (30.81%) had normal platelet counts, and 256 (69.18%) had thrombocytopenia (p<0.05). The mild, moderate and severe thrombocytopenia were found in 39 (10.5%), 180 (48.6%) and 37 (10%) respectively (p<0.05). Conclusions: We found high frequency of mild to moderate thrombocytopenia in the Plasmodium falciparum malaria. Finding of thrombocytopenia is of diagnostic help as it raises the suspicion of malaria. Keywords: Thrombocytopenia, Malaria, Plasmodium falciparum